Preparation method of high-performance sodium storage composite material based on carbon-coated nickel disulfide core-shell nano-box structure

By adopting a carbon-coated nickel disulfide core-shell nanobox structure in the sodium ion battery electrode material, the problem of volume expansion and poor conductivity of the TMSs electrode material during circulation is solved, and a high-performance sodium storage composite material is realized.

CN119612609AActive Publication Date: 2025-03-14UESTC (SHENZHEN) ADVANCED RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411710970.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The problem of volume expansion and poor conductivity of transition metal sulfide (TMSs) electrode materials of sodium ion batteries during circulation.

Method used

A high-performance sodium storage composite material based on carbon-coated nickel disulfide core-shell nanobox structure is used to form a NiS2 core-shell nanobox structure composite material wrapped in nitrogen-doped carbon nanofibers by electrospinning and vulcanization treatment.

Benefits of technology

This material effectively adapts to the volume expansion of NiS2 during charging and discharging, and significantly improves the conductivity of the material, showing excellent sodium storage performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612609A_ABST
    Figure CN119612609A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nano-box structure, and belongs to the technical field of preparation of sodium ion battery negative electrode materials. The invention aims to alleviate volume expansion of a transition metal sulfide (TMSs) electrode material in a circulation process and solve the problem of relatively poor conductivity through the design of a sodium ion battery negative electrode material structure. The preparation method comprises the following steps: firstly, carrying out electrostatic spinning on a nickel-based metal organic compound (Ni-MOC) precursor synthesized by an oil bath method, and then carrying out sulfuration treatment in an argon atmosphere to obtain the carbon-coated NiS2 core-shell nano-box structure composite material. By utilizing the unique hollow interior and protective carbon layer structure, the volume expansion of NiS2 in the charging and discharging process is effectively adapted, and meanwhile, the conductivity and structural stability of the material are remarkably improved, so that excellent electrochemical performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of sodium ion battery electrode materials, and specifically relates to a method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure. Background Art

[0002] The development of battery technology has become an important focus to meet the growing global energy demand. Sodium-ion batteries are abundant and widely distributed, and as a substitute for traditional lithium-ion batteries, they have low cost and great potential in large-scale applications. However, the relatively large ionic radius of sodium ions (Na + The radius is Li + The radius is ) leads to slow kinetic diffusion and significant volume change, which can reduce rate performance and cycling stability. Therefore, it is urgent to develop high-performance anode materials for sodium-ion batteries to meet application requirements.

[0003] To this end, researchers have synthesized a variety of different anode materials, including carbonaceous materials, alloys, metal oxides, sulfides, selenides, and phosphides. Among these materials, transition metal sulfides (TMSs) have attracted much attention due to their high sodium storage capacity. However, these materials undergo huge volume changes during sodium storage, resulting in structural damage and rapid decay of specific capacity. In particular, nickel disulfide (NiS2), one of the widely studied members of TMSs, has a high theoretical capacity (879 mAh g -1 ), but still face challenges such as poor conductivity and volume expansion. Summary of the invention

[0004] The purpose of the present invention is to alleviate the volume expansion of transition metal sulfide (TMSs) electrode materials during the cycle process and solve the problem of poor conductivity through the design of the negative electrode material structure of sodium ion batteries.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure comprises the following steps:

[0007] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000;

[0008] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0009] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0010] Step 4: Disperse 0-600 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0011] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV with a 0.03 mm nin -1 Stable filament speed drive;

[0012] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:0-5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The temperature was heated at a rate of 450-750°C and maintained for 3 h to promote the sulfurization reaction, and finally a carbon-coated NiS2 core-shell nanobox structure composite material was obtained.

[0013] Preferably, in the above technical solution, the amount of Ni-MOC in step 4 is 412 mg.

[0014] In the above technical solution, the mass ratio in step 6 is 1:5.

[0015] In the above technical solution, the vulcanization temperature in step 6 is 450°C.

[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0017] 1. The present invention successfully synthesized a NiS2 core-shell nanobox structure composite material wrapped by nitrogen-doped carbon nanofibers (denoted as NiS2@NC). This material combines the high capacity of NiS2 and the high conductivity of the nitrogen-doped carbon matrix. Specifically, this unique structure not only effectively adapts to the volume expansion of NiS2 during the charge and discharge process, but also significantly improves the conductivity of the material.

[0018] 2. The NiS2 core-shell nanobox structure composite material (denoted as NiS2@NC) wrapped with nitrogen-doped carbon nanofibers prepared in the present invention has excellent sodium storage performance when used as a sodium storage anode with a current density of 1A g -1 After 300 charge-discharge cycles, the material showed a capacity of 585 mAh g-1 The high reversible capacity of the 2000nm process was 95.8%, with a capacity retention rate of 95.8% compared with the initial cycle. In addition, even at 5A g -1 At a high current density of 1.3 Å, the material still maintained a charge capacity of 486 mAh g after 900 cycles. -1 capacity.

[0019] 3. The preparation technology of the present invention is simple and easy to operate, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an electron microscope image of the sodium ion battery electrode material of the present invention;

[0021] Figure 2 This is a physical characterization diagram of the sodium ion battery electrode material of the present invention;

[0022] Figure 3 The X-ray diffraction patterns of Examples 2 and 3 of the present invention;

[0023] Figure 4 This is a test diagram of the electrochemical performance of the sodium ion battery electrode material of the present invention;

[0024] Figure 5 The cyclic voltammetry test diagram of the sodium ion battery electrode material of the present invention and the corresponding fitting analysis;

[0025] Figure 6 The electrochemical impedance test diagram of the sodium ion battery electrode material of the present invention and the corresponding fitting analysis;

[0026] Figure 7 This is a density functional theory (DFT) analysis diagram of the sodium ion battery electrode material of the present invention. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.

[0028] A method for preparing a sodium ion battery material with excellent sodium storage performance comprises the following steps:

[0029] Example 1

[0030] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000;

[0031] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0032] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0033] Step 4: Disperse 412 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0034] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive;

[0035] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The reaction mixture was heated at a rate of 450 °C until it reached 450 °C and maintained for 3 h to promote the sulfurization reaction, ultimately obtaining a carbon-coated NiS2 core-shell nanobox structure composite material.

[0036] Example 2

[0037] Step 1: 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone are added to 180 ml of anhydrous ethanol, and then stirred on a magnetic stirrer for 30 min to ensure that the mixture is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000; 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone (molecular weight is 58,000) are added to 180 ml of anhydrous ethanol, and then stirred on a magnetic stirrer for 30 min to ensure that the mixture is completely dissolved;

[0038] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0039] Step 3: The green precipitate of Ni-MOC was separated by centrifugation, the resulting precipitate was collected, washed three times with ethanol, and then dried at 60°C overnight to prepare Ni-MOC powder;

[0040] Step 4: Place the Ni-MOC powder obtained in step 3 downstream of the ceramic boat, and add a certain amount of sulfur powder upstream, with the mass ratio of Ni-MOC powder to sulfur powder being 1:5. Then place the ceramic boat in a tube furnace and heat it at 1°C min in an argon atmosphere. -1The reaction mixture was heated at a rate of 400 °C until it reached 450 °C and maintained for 3 h to promote the sulfidation reaction, ultimately obtaining pure NiS2 electrode material (denoted as Pure NiS2).

[0041] Example 3

[0042] Step 1: 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone were added to 180 ml of anhydrous ethanol, and then stirred on a magnetic stirrer for 30 min to ensure that the mixture was completely dissolved, wherein the molecular weight of polyvinyl pyrrolidone was 58,000;

[0043] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0044] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0045] Step 4: Take 0 mg of the Ni-MOC powder prepared in step 3 and disperse it in 2.5 ml of dimethylformamide solvent, then add 206 mg of polyacrylonitrile to the solution and stir at room temperature for 48 h until it is completely dissolved;

[0046] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain pure PAN fibers. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min. -1 Step 6: Place the pure PAN fiber obtained in step 5 in a ceramic boat, and then place the ceramic boat in a tube furnace in an argon atmosphere at 1 ° C min -1 The sample was heated at a rate of 450 °C and maintained at that temperature for 3 h to promote the carbonization reaction, and finally nitrogen-doped carbon nanofibers (denoted as NC) were obtained.

[0047] Example 4

[0048] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of polyvinyl pyrrolidone is 58,000:

[0049] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0050] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0051] Step 4: Disperse 200 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0052] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive;

[0053] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The reaction mixture was heated at a rate of 450° C. until it reached 450° C. and maintained for 3 h to promote the sulfurization reaction, thereby finally obtaining a carbon-coated NiS2 core-shell nanobox structure composite material. Compared with Example 1, the content of the active substance NiS2 was reduced.

[0054] Example 5

[0055] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000;

[0056] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0057] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0058] Step 4: Disperse 600 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0059] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive;

[0060] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The temperature was heated at a rate of 450° C. until it reached 450° C. and maintained for 3 h to promote the sulfurization reaction, and finally a carbon-coated NiS2 core-shell nanobox structure composite material was obtained. Compared with Example 1, the content of active substance NiS2 was increased.

[0061] Example 6

[0062] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of polyvinyl pyrrolidone is 58,000:

[0063] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0064] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0065] Step 4: Disperse 412 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0066] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive;

[0067] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The reaction mixture was heated at a rate of 100 ° C. until it reached 600 ° C. and maintained for 3 h to promote the sulfurization reaction, and finally a carbon-coated NiS2 core-shell nanobox structure composite material was obtained. Compared with Example 1, the sulfurization temperature was increased.

[0068] Example 7

[0069] Step 1: Add 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone to 180 ml of anhydrous ethanol, and then stir the mixture on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000;

[0070] Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours;

[0071] Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder;

[0072] Step 4: Disperse 412 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved;

[0073] Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive;

[0074] Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The temperature was heated at a rate of 100 °C until it reached 750 °C and maintained for 3 h to promote the sulfurization reaction, and finally a carbon-coated NiS2 core-shell nanobox structure composite material was obtained.

[0075] Compared with Example 1, the vulcanization temperature was increased.

[0076] Figure 1 As shown in the electron microscope image of Example 1, the precursor of the material - nickel-based metal organic compound (Ni-MOC) is first synthesized by an oil bath method, then electrospinning is performed, and finally a sulfurization treatment is performed under an argon atmosphere to generate a stable composite material (NiS2@NC) with a carbon-coated nickel disulfide core-shell nanobox structure. Figure 1 A and Figure 1 Figure b shows the morphology of polyvinyl pyrrolidone (PAN)-wrapped Ni-MOC. The prismatic shape of Ni-MOC is well preserved in the PAN fibers, forming a mesh-like interconnected network. After sulfurization, the NiS2@NC product retains its original structure ( Figure 1(c and d). The outer carbon shell not only acts as a protective layer against volume change during sodium storage but also helps Ni-MOC maintain its morphology during the sulfidation process. Figure 1 The TEM image in e further confirms that NCs effectively wrap around NiS2 and the core-shell structure of the NiS2 particles inside. Figure 1 As shown in (f), the lattice planes of NiS2@NC are clearly observed by high-resolution transmission electron microscopy (HRTEM), revealing a 0.255 nm interplanar spacing corresponding to the (210) plane of NiS2 and a 0.137 nm interplanar spacing corresponding to the (410) plane. Energy dispersive X-ray spectroscopy (EDS) element mapping shows that Ni, S, N, C, and O elements are uniformly distributed in NiS2@NC ( Figure 1 (g).

[0077] Figure 2 and Figure 3 The physical characterization diagram of the battery material of the present invention is obtained from the X-ray electron diffraction pattern (XRD; Figure 2 In a), it can be seen that all characteristic diffraction peaks of NiS2@NC synthesized in Example 1 can be attributed to cubic phase NiS2 (PDF#11→0099), and the peaks at 27.2°, 31.6°, 35.3°, 38.8°, 45.3° and 53.6° correspond to (111), (200), (210), (211), (220) and (311) crystal planes, respectively. Pure NiS2 synthesized in Example 2 also presents the same diffraction pattern, and there is no obvious shift in the peak position, while the NC synthesized in Example 3 has no visible diffraction peaks, indicating that it is amorphous in nature ( Figure 3 ). X-ray photoelectron spectroscopy (XPS) was used to study the elemental composition and valence state of NiS2@NC. Figure 2 As shown in the full spectrum in b, the sample contains Ni, S, C, N and O elements. Figure 2 The high-resolution Ni 2p spectrum in (c) shows that the Ni 2+ 2p 1 / 2 , Ni 2+ 2p 3 / 2 , Ni 3+ 2p 1、2 and Ni 3+ 2p 3 / 2 Orbital peak. 3+ The presence of Ni in the material may be due to 2+ Oxidized to Ni 3+ In addition, two typical satellite peaks were observed at 861.48 and 880.78 eV. Figure 2The S 2p spectrum of NiS2@NC in (d) shows that the two main peaks at 162.48 and 163.58 eV correspond to the S 2p 3 / 2 and S 2p 1 / 2 , indicating the presence of Ni-S bonds. In addition, the peak at 164.48 eV is associated with the SS bond of α-S8, indicating the possible presence of residual sulfur during the sulfurization process. The peaks at 168.4 and 169.5 eV are associated with SO bonds and sulfate bonds, respectively. Figure 2 As shown in Figure e, the C 1s spectrum shows three different peaks at 284.78, 286.48 and 289.08 eV, corresponding to the CC / C=C bond, CO / C--N / CS bond and C=O bond, respectively. Figure 2 As shown in Figure 5, the peaks observed in the N 1s spectrum at 398.28, 399.98, and 403.38 eV can be attributed to three different nitrogen species: pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen. In addition, nitrogen doping not only helps to increase the presence of defects, but also provides a new source of defects for Na + The insertion creates additional active sites and also helps to further improve the electrical conductivity in the carbon matrix.

[0078] In order to study the reaction mechanism of NiS2@NC synthesized in Example 1 during sodium storage, the performance of the assembled sodium ion half-cell was analyzed by cyclic voltammetry (CV). Figure 4 Figure a depicts the voltage drop at 0.1 mV s -1 The first three cycles of cyclic voltammetry curves of NiS2@NC were obtained at a scan rate of 1.27 V and 0.67 V, respectively, corresponding to the addition of Na + Inserted into the NiS2 lattice to form Na x NiS2, which is then converted to Ni and Na2S. The decomposition of the electrolyte leads to the formation of a solid electrolyte interface (SEI) film, and Na + During the subsequent desodiumization process, the oxidation peaks at 1.79 V and 2.07 V correspond to the partial reversible conversion of Ni and Na2S to Na + In addition, except for the initial cycle, the oxidation peaks and reduction peaks of the subsequent cyclic voltammetry curves almost completely overlap, indicating that the NiS2@NC electrode exhibits excellent electrochemical reversibility during the continuous sodium insertion and deinsertion process. Similarly, Figure 4 Figure b shows the NiS2@NC at 0.1A g -1 The first three cycles of constant current charge-discharge (GCD) curves at a current density of . The NiS2@NC electrode exhibited a charge-discharge rate of 813 mAh g in the first cycle. -1 The discharge capacity and 738mAh g -1The charge capacity of the prepared NiS2 electrode was 828 mAh g / cm2, which resulted in a high initial coulombic efficiency (ICE) of 90.8%. The irreversible loss of capacity was attributed to the formation of a solid electrolyte interface (SEI) film, which was caused by the decomposition of the electrolyte. In contrast, the pure NiS2 prepared in Example 2 and the NC prepared in Example 3 showed 828 mAh g / cm2 and 653 mAh g / cm2, respectively. -1 and 531 / 304mAh g -1 The discharge / charge capacity of the 2000 MW PV is 78.9% and 57.2%, respectively. Figure 4 ). Figure 4 Figure c depicts the NiS2@NC, pure NiS2, and NC at different current densities (0.1-5Ag -1 ) under the condition of high current density. It can be clearly seen from the figure that the rate performance of NiS2@NC is better than that of pure NiS2 and NC. When the current density is 0.1, 0.2, 0.5, 1, 2 and 5A g -1 When the average reversible capacities of NiS2@NC are 514, 515, 507, 494, 476 and 444 mAh g -1 Then, when the current density returned to 0.1A g -1 When the average reversible capacity rises to 563 mAh g -1 . Notably, in the first 10 cycles, the reversible capacity of pure NiS2 was found to be higher than that of NiS2@NC, which may be due to the absence of inactive amorphous carbon in the former. However, its relatively low conductivity and the presence of aggregated NiS2 particles led to a rapid capacity decay. In addition, the capacity of NC was relatively stable, but much lower compared to the other two samples. The excellent rate performance of NiS2@NC can be attributed to the unique NiS2 core-shell nanobox structure protected by an outer carbon shell, which is also connected by a three-dimensional conductive network of carbon nanofibers, combining the high capacity of pure NiS2 and the relatively high conductivity of NC. In addition, Figure 4 Figure d shows the constant current charge-discharge curves of NiS2(@NC at different current densities. These curves show similar shapes and maintain a consistent charge-discharge voltage platform, indicating that the NiS2@NC electrode maintains good stability at different current densities and has good stability under Na + The polarization during the deintercalation / intercalation process is minimal. Figure 4 Figure e shows the results of all samples at 1A g -1 In the initial cycle, the specific capacity of NiS2@NC is 611 mAh g -1 , while pure NiS2 and NC only showed 439 and 255 mAh g -1After 300 cycles, the reversible capacity of NiS2@NC remained at 585 mAh g -1 (Pure NiS2 is 365mAh g -1 , NC is 330mAh g -1 ), with a capacity retention rate of up to 95.8%. With the increase of current density ( Figure 4 f), it is obvious that the NiS2@NC electrode -1 The battery also exhibited excellent stability and high capacity at a current density of 1.3 Å, maintaining 486 mAh g after 900 cycles. -1 , the capacity retention rate was 94.1% compared with the initial cycle.

[0079] In order to comprehensively study the kinetic characteristics of the NiS2@NC electrode synthesized in Example 1 during the sodium ion storage process, the -1 Cyclic voltammetry tests were performed in the range of Figure 5 From the results in a, it can be seen that as the scan rate increases, the shape of the redox peak remains unchanged and the shift of the peak position is negligible. This indicates that the polarization effect of the electrode is greatly suppressed. The charge storage behavior is analyzed by examining the relationship between the peak current (i) and the scan rate (v). The calculation formula can be expressed as the equation:

[0080] i=av b

[0081] log i=blog v+log a

[0082] Where a and b are adjustable parameters. Figure 5 In b, by fitting the relationship between log i and log v, the b values ​​of the cathode and anode can be determined to be 1.07 and 1.06, respectively. This indicates that the sodium storage of NiS2@NC is mainly capacity-controlled. In addition, based on the following formulas, the capacitance contribution (k1v) and diffusion contribution (k2v 1 / 2 ) for quantitative analysis:

[0083] i=k1v+k2v 1 / 2

[0084] Figure 5 Figure c shows the voltage drop from 0.1mV s -1 To 1mV s -1 The contributions of the capacitance ratios at different scan rates are 89.4%, 92.4%, 93.5%, 94.8%, 96.0% and 96.5% respectively. Based on the above electrochemical reaction kinetics analysis, the dominant capacitance effect significantly enhances the Na content in the NiS2@NC electrode material under high rate conditions. +In addition, at 1mV s -1 In the cyclic voltammetry curve of the electrode obtained at a scan rate of , the shaded area indicates that the capacitive storage of sodium contributes 96.5% of the total capacity ( Figure 5 (d)

[0085] Subsequently, electrochemical impedance spectroscopy (EIS) was used to study the electron transport and sodium ion diffusion in the electrode. The Nyquist plot obtained before the cycling measurement is shown in Figure 2. Figure 6 As shown in a. The EIS curve is usually composed of a semicircle in the high-frequency region and a linear slope in the low-frequency region. The former represents the resistance (Rs) and charge transfer resistance (Rct) of the SEI film, while the latter represents the resistance to sodium ion diffusion. The Rct value of NiS2@NC (76.1Ω) synthesized in Example 1 is significantly smaller than that of pure NiS2 (268.2Ω) synthesized in Example 2 and NC (92.2Ω) synthesized in Example 3. This further indicates that the three-dimensional conductive network of NiS2@NC significantly improves the conductivity. In addition, the calculated diffusion coefficients of NiS2@NC, pure NiS2 and NC The values ​​are 1.02×10 -12 cm 2 s -1 , 5.86×10 -13 cm 2 s -1 and 5.82×10 -13 cm 2 s -1 This confirms that the combination of NC and NiS2 can significantly enhance the diffusion of sodium ions in the NiS2@NC electrode, showing great potential for improving performance in energy storage applications.

[0086] In order to further explore the potential factors for the excellent electrochemical performance of the NiS2@NC heterostructure synthesized in Example 1, we conducted an in-depth analysis using density functional theory (DFT). Figure 7 As shown, among the three models, the prepared NiS2@NC exhibits the highest sodium ion adsorption energy and charge density at the Fermi level. These results indicate that constructing a core-shell nanobox heterostructure effectively promotes charge transfer and ion diffusion and significantly enhances the adsorption capacity of sodium ions, thereby achieving excellent electrochemical performance.

[0087] In summary, the present invention successfully synthesized a NiS2 core-shell nanobox structure composite material wrapped by nitrogen-doped carbon nanofibers. This material combines the high capacity of NiS2 and the high conductivity of the nitrogen-carbon matrix. Specifically, this unique structure not only effectively adapts to the volume expansion of NiS2 during the charge and discharge process, but also significantly improves the conductivity of the material. When used as a sodium storage anode, after 300 charge and discharge cycles at a current density of 1A g -1 When the material shows 585mAh g -1 The high reversible capacity of the 2000nm process was 95.8%, with a capacity retention rate of 95.8% compared with the initial cycle. In addition, even at 5A g -1 At a high current density of 1.3 Å, the material still maintained a charge capacity of 486 mAh g after 900 cycles. -1 The capacity of the heterojunction structure is 1.34 W, which confirms its exceptional cycling stability. According to the calculation results of theoretical analysis, the special sodium storage performance of this heterojunction structure can be attributed to the charge redistribution phenomenon occurring at the interface. The present invention provides innovative solutions and methods to address the challenges of volume expansion and conductivity faced by nickel sulfide in electrochemical applications.

[0088] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure, characterized in that: The following steps are involved: Step 1: 1.152 g of nickel acetate tetrahydrate and 3.15 g of polyvinyl pyrrolidone are added to 180 ml of anhydrous ethanol, and then the mixture is stirred on a magnetic stirrer until it is completely dissolved, wherein the molecular weight of the polyvinyl pyrrolidone is 58,000; Step 2: Transfer the solution obtained in step 1 to an oil bath at 85°C and stir for 24 hours; Step 3: Separate the green precipitate of Ni-MOC by centrifugation, collect the resulting precipitate, wash it with ethanol, and then dry it at 60°C overnight to prepare Ni-MOC powder; Step 4: Disperse 0-600 mg of the Ni-MOC powder prepared in step 3 in 2.5 ml of dimethylformamide solvent, add 206 mg of polyacrylonitrile to the solution, and stir at room temperature until completely dissolved; Step 5: The final solution obtained in step 4 was used for electrospinning to obtain the composite material Ni-MOC@PAN. During the spinning process, the distance between the nozzle and the aluminum foil was kept at 12 cm, and the nozzle was 13 kV at a speed of 0.03 mm min -1 Stable filament speed drive; Step 6: Place the composite material Ni-MOC@PAN obtained in step 5 downstream of the ceramic boat, and add sulfur powder upstream, the mass ratio of the composite material to the sulfur powder is 1:0-5, and then place the ceramic boat in a tube furnace and heat it at 1℃min in an argon atmosphere. -1 The temperature was heated at a rate of 450-750°C and maintained for 3 h to promote the sulfurization reaction, and finally a carbon-coated NiS2 core-shell nanobox structure composite material was obtained.

2. The method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure according to claim 1, characterized in that: The Ni-MOC is 412 mg.

3. The method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure according to claim 1, characterized in that: The mass ratio of the composite material to the sulfur powder is 1:

5.

4. The method for preparing a high-performance sodium storage composite material based on a carbon-coated nickel disulfide core-shell nanobox structure according to claim 1, characterized in that: The vulcanization temperature is 450°C.

Citation Information

Patent Citations

  • Preparation method for nickel sulfide nano-spheres and application thereof

    CN109110827A

  • Universal preparation method for synthesizing carbon-coated nickel metal compound with various morphologies

    CN112010360A

  • Preparation method for synthesizing heteroatom-doped nickel sulfide with various morphologies by using metal organic framework

    CN112010361A

  • Carbon-coated metal sulfide with core-shell structure as well as preparation method and application of carbon-coated metal sulfide

    CN117303468A